The relationship between current and former shift work and the metabolic syndrome - Puttonen, Sampsa; Viitasalo, Katriina; Härmä, Mikko (Scandinavian Journal of Work, Environment & Health, 2012)
' ' OBJECTIVE ': 'The occurrence of possible health hazards among former shift workers is not well-known. We studied associations of former and current shift work with the metabolic syndrome (MetS). ' ' METHODS ': 'Participants were 1811 full-time employees of a large airline company (1009 men). Working times were categorized into five groups: day worker [N=297 (the reference group)], former shift worker (N=341), 2-shift worker (N=418), night-shift worker (N=283), and in-flight worker (N=472). MetS was measured by the International Diabetes Federation (IDF) criteria and the National Institute of Health Adult Treatment Panel III (NCEP) guideline. The prevalence of the syndrome in the study population was 28.5% and 20.8%, respectively. ' ' RESULTS ': 'Among male former shift workers, MetS was more prevalent compared to male day workers [IDF: age-adjusted odds ratio (OR) 2.13, 95% confidence interval (95% CI) 1.35–3.37; NCEP: OR 1.83, 95% CI 1.13–2.96]. Associations did not change after additional adjustments for education, smoking, physical activity, alcohol consumption, and insomnia symptoms (IDF: OR 2.00, 95% CI 1.26–3.19; NCEP: 1.67, 95% CI 1.02–2.72). Male 2-shift workers also had an elevated risk of IDF-defined MetS (OR 1.64, 95% CI 1.06–2.55) but the association weakened in the fully adjusted analyses (OR 1.48, 95% CI 0.93–2.24). Prevalence of the MetS was marginally significantly higher among night-shift work (IDF: OR 1.51, 95% CI 0.95–2.34) and was attenuated further with additional adjustments (OR 1.37, 95% CI 0.84–2.22). Among women, no significant differences in prevalence of the MetS between day work and shift work were observed. ' ' CONCLUSION ': 'Findings of the cross-sectional study suggest that MetS diagnosed by standardized criteria is more prevalent among former male shift workers than current day workers who have never worked in shifts.
Keywords: cardiovascular risk factor; epidemiology; metabolic syndrome; shift work